PENDEKATAN DALAM SUPERVISI PENDIDIKAN : Introduction, Research Method, Study Theory, Research Results and Discussion, Conclusion - Binti Arifah Nurhasanah; Diah Zuyyina Rahma; Subandi Subandi (CV. ALIM'SPUBLISHING, 2025)
The purpose of this study is to investigate different methods of educational supervision that can raise the standard of instruction in classrooms. Enhancing the general quality of education and fostering teacher professionalism are two major goals of educational oversight. This study examines different theories and practices of educational supervision in Indonesia using a qualitative method and a literature study methodology. A review of the literature revealed that there are a number of ways to conduct educational supervision, including competency-based, learning-based, and collaborative supervision. Each of these techniques has benefits and drawbacks when it comes to execution. The results of this study show that enhancing teaching quality and teacher professionalism can be greatly aided by the appropriate supervision strategy. The research's implication is that, in order to accomplish the best possible educational outcomes, it is critical to adopt a supervision strategy that is suitable for the school environment and the demands of teacher development. It is intended that educators and education management will use this research as a guide when creating efficient supervision plans for students at different educational levels.